Influence of Taxes on Capital Flows and Foreign Direct Investment - Aisyah, Siti (Golden Ratio of Taxation Studies, 2025)
This qualitative literature review investigates the influence of taxation policies on capital flows and Foreign Direct Investment (FDI). The research aims to provide a comprehensive understanding of the relationship between taxes and international investment patterns, focusing on theoretical frameworks, empirical evidence, and policy implications. The research methodology involves a systematic search and analysis of relevant scholarly literature from reputable academic databases. Thematic analysis is employed to identify recurring themes and patterns in the literature, ensuring rigor and reliability in the findings. The results reveal that taxes play a significant role in shaping FDI inflows, with higher tax rates generally deterring foreign investors. However, the impact of taxes on FDI varies depending on contextual factors such as economic development, sectoral composition, and institutional quality. Mechanisms through which taxes influence investment behavior include their direct impact on after-tax profitability, as well as indirect effects on investor perceptions of risk and return. Policy implications highlight the importance of tax competitiveness, institutional quality, and complementary measures in attracting and retaining FDI.